Feminization of the Teaching Profession and the Androcentrism of the Polish Language – Will “Any Bread Be Made of This Flour”? Developmental Chances for Women’s Potentials - Górnikowska-Zwolak, Elżbieta (Pedagogika Społeczna Nova, 2025)
A critical review of educational institutions and processes using the paradigms of social anthropology, feminist and social constructivism allows us to perceive an extremely important and rarely addressed problem: What are the opportunities for developing the potentials of girls and women with the participation of a school that uses androcentric language? The author uses a term to which Helena Radlińska attributed the greatest importance in upbringing: the invisible environment. And it makes us realize that the native language is the most important element of the invisible living environment, at the same time being an invisible environment itself. Its meaning is not realized by teachers and tutors. Therefore it is worth looking at female teachers (representatives of a profession dominated by women) who, immersed in language and unaware of its power, stand guard over the patriarchal world, upholding the dominance of men.